A turning point in the development of Norwegian economics: The establishment of the University Institute of Economics in 1932 - Olav Bjerkholt (University of Oslo, Department of Economics, 2000)
A confluence of circumstances led to the foundation of the University Institute of Economics in Oslo in 1932. Ragnar Frisch was the kingpin in this development. After having been appointed professor of economics and statistics by an unusual decision by the Storting in 1932 he decided to decline an attractive offer of a permanent professorship from Yale University. The decisive factor was the prospect of establishing an empirical research institute at the University, financed by Rockefeller Foundation. The outcome was of major importance for the development of economics and empirical social science in Norway.
Keywords: 330; Ragnar Frisch; Rockefeller Foundation; Norwegian economics; Wirtschaftswissenschaft; Wirtschaftshochschule; Geschichte; Norwegen